GEMSHiDa Apps: Explore Hindu-Buddha History Materials with an Android Game for Social Studies Students in Junior High School - Mey Lafaiza Sukmaning Haresa; Bayu Kurniawan; Mohamed Jefferi bin Haji Mat Lazim (UIN Fatmawati Sukarno Bengkulu, 2024)
One potential learning tool for engaging students in play while providing comprehensive information on Hindu-Buddhist content is an educational game. This study focuses on developing the GEMSHiDa app, an educational game centered on Hindu-Buddhist history for Android devices, intended for social studies students in Junior Hight School. Following a research and development (R&D) approach using the ADDIE model, validation from two experts rated the app's teaching material as